ESTIMATION OF THERMO CYCLE LIFETIME OF GAS-TURBINE ENGINES'S HIGH-TEMPERATURE MATERIALS BY HYPOTHESIS OF BEING LINEAR DAMAGES SUMMATION - Кулик, М.; Кучер, О.; Ковешніков, М.; Дубровський, С.; Петрук, Я. (Science-based technologies, 2011)
Practical possibility of estimation of thermo cycle lifetime of materials in the critical points of details of GTE «hot part», that limits the resource of modern engines is considered . Such problem arises on the stages of engine designing, manufacturing and engine development on the set resource. Possibility of estimation on the stages of the GTE creation arises up with the use of hypothesis of being damages linear summation of the GTE materials, taking into account standard descriptions of long duration durability and specified coefficients of relative longevity. They, as it is known, never are equals unity (aN  1), to a great extent specified in this work, and can be got on the measure of the GTE creation for the newest materials.